LEGAL AND ECONOMIC MECHANISMS FOR ENSURING SECURITY AND CONDITIONS FOR DIGITAL TRANSFORMATION IN THE REPUBLIC OF UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2024)
Digital transformation is rapidly reshaping economies and societies worldwide, presenting both opportunities and challenges for nations. In Uzbekistan, the government has embraced digitalization as a key pillar of its national development strategy, spearheaded by initiatives like the Digital Uzbekistan 2030 program. This paper examines the legal and economic mechanisms necessary to ensure security and create favorable conditions for digital transformation in the country. It explores the current state of digitalization, highlights security concerns, and analyzes the regulatory and economic policies driving digital adoption. By addressing challenges such as the digital divide, cybersecurity threats, and workforce adaptation, the paper underscores the need for a balanced approach that integrates innovation, inclusivity, and security.